City of lost souls - Clare, Cassandra (New York : Walker Books, 2015)
As mysterious murders threaten the new peace between Shadowhunters and Downworlders, only Simon, the Daylighter vampire, can help bring both groups together.
Ages 14 up.
Keywords: Vampires -- Juvenile fiction; Demonology -- Juvenile fiction; Magic -- Juvenile fiction; Demonology; Magic; Vampires; New York (N.Y.) -- Juvenile fiction; New York (State) -- New York; Fiction; Juvenile works; Occult fiction